The Use of Quillbot AI to Enhance Writing Skills in Descriptive Text on PBI Students 4th Semester At STKIP Bina Mutiara Sukabumi - Sugara, Ria Dewi Hudayani; Diennur, Usman; Ependi, Ajimatullah (Journey: Journal of English Language and Pedagogy, 2025)
Writing is one of the important skills that students should have in school. Writing activities, especially writing descriptive text, become an integral part of the learning process.  The phenomenon in the field shows that students still often have difficulties in creating descriptive texts, such as confusion in using vocabulary, difficulty finding ideas, improper writing structure, etc. This research aims to enhance students' writing skills by using QuillBot AI. The approach in this research uses a quantitative method and uses a pre-experimental, approach with a single group class. The instruments that were utilized were a writing test and a questionnaire via Google form with purposive sampling of PBI students in the fourth semester in regular class, consisting of 20 students from PBI students in the fourth semester. This research uses QuillBot AI as media and fourth-semester students as research samples, which makes this research different from previous research. The results show that employing QuillBot AI to write descriptive texts has an effect on students' writing abilities, with 95.53% of students' responses falling into the Strongly Agree. Additionally, based on the average pre-test in mean result is 76,90 and post-test mean score is in 84,70 and the paired sample t-test result is p-value is less than the significance level (0,05) its mean  the students' writing skills have improved.